An antagonistic role of clock genes and lima1 in kidney regeneration - Xian He; Ziming Wang; Linxi Cheng; Han Wang; Yuhua Sun (Communications Biology)
Abstract The circadian clock genes are known important for kidney development, maturation and physiological functions. However, whether and how they play a role in renal regeneration remain elusive. Here, by using the single cell RNA-sequencing (scRNA-seq) technology, we investigated the dynamic gene expression profiles and cell states after acute kidney injury (AKI) by gentamicin treatment in zebrafish. The core clock genes such as per1/2 and nr1d1, which encode transcriptional repressors of the circadian system, are strongly induced in the proximal tubule epithelial cells (PTECs). By generating mutant zebrafish lines, we show that per1a and nr1d1 are required for proper renal regeneration, by facilitating the expression of renal progenitor cell (RPC) genes. In per1a and nr1d1 mutants, the expression of RPC genes and the number of RPCs were decreased, resulting in a marked delay in nephron regeneration. lima1a, which encodes a cytoskeleton binding protein that functions to negatively regulate epithelial to mesenchymal transition (EMT), is identified as the direct target of the clock proteins. Down-regulation of lima1a is associated with enhanced EMT, increased expression of cell migration- and RPC markers, and accelerated nephron regeneration. We propose that per1a and nr1d1 are important for the formation of nephrongenic RPCs by repressing lima1a. Our findings using zebrafish provide important insights into the roles of the clock genes in kidney repair.